(untitled) (Journal of Hama University, 2024)
This study was conducted to evaluate the effect of adding different levels of wheat bran in broiler diets on some productivity indicators.This study was carried out on a total of 180- day-old chicken Ross 308. Birds were randomly divided into three groups according to the complete random design, each group included three replicates, (20 birds in each). Bird’s groups fed ad libitum on iso-protein and iso-energy diets for 42 days as follows: The first group (T1) was fed the control diet (without adding wheat bran), while the birds of the second (T2) and third (T3) groups were fed diets to which 3 and 5% wheat bran was added, respectively. The results of the study showed that there are no significant differences (P> 0.05) in total mortality rates and feed consumption among the studied groups. It was noted that there are no significant differences (P> 0.05) in average body weight and body weight gain of the second group (T2), while feed conversion ratio decreased significantly (P≤0.05) during the last two weeks of the birds’ age, as compared to the control group. The results also confirmed that there is a significant decrease (P≤0.05) in average body weight and body weight gain of the third group (T3) during the first week of birds age, in addition to a significant increase in feed conversion ratio during the first two weeks of age compared to the control group. In conclusion, wheat bran could be added up to 3% in broiler diets for improving feed conversion efficiency.